PENGGUNAAN INSTRUMEN ASESMEN LITERASI BERMUATAN KARAKTER DENGAN MENGGUNAKAN METODE LINK AND MATCH PADA MAHASISWA IKIP SILIWANGI - Latifah - Latifah; Siti Salamah Azzahra (STKIP Siliwangi, 2022)
The purpose of this study was to determine the use of character-laden literacy assessments using the link and match method and to determine the relationship between student test results regarding character-loaded literacy assessments and student questionnaire results. The method used in this research is descriptive qualitative method, which is a research method that makes a systematic, accurate, and factual overview of a fact, its nature, and the relationship between the phenomena studied. The data analysis technique in this study, namely the test technique, is to determine the results of character-laden literacy assessments by using the link and match method and the questionnaire technique used to determine the relationship between the results of literacy assessment tests containing character and the results of student questionnaires. The subjects in this study were students of IKIP Siliwangi class B1 class of 2019 Indonesian Language Education Study Program. The results obtained from the student literacy assessment were 72%. And the results of student questionnaires about the average character of 86.5%. Based on the descriptive analysis criteria table, the percentage for literacy assessment is in the high category criteria, while for the questionnaire filled with characters the percentage is in the very good criteria.